Metal and Nonmetal Codoped 3D Nanoporous Graphene for Efficient Bifunctional Electrocatalysis and Rechargeable Zn–Air Batteries. Issue 19 (28th March 2019) - Qiu, Hua‐Jun; Du, Peng; Hu, Kailong; Gao, Jiaojiao; Li, Huanglong; Liu, Pan; Ina, Toshiaki; Ohara, Koji; Ito, Yoshikazu; Chen, Mingwei
Abstract: Developing bifunctional electrocatalysts with high activities and long durability for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is crucial toward the practical implementation of rechargeable metal–air batteries. Here, a 3D nanoporous graphene (np‐graphene) doped with both N and Ni single atoms/clusters is reported. The predoping of N by chemical vapor deposition (CVD) dramatically increases the Ni doping amount and stability. The resulting N and Ni codoped np‐graphene has excellent electrocatalytic activities for both the ORR and the OER in alkaline aqueous solutions. The synergetic effects of N and Ni dopants are revealed by density functional theory calculations. The free‐standing Ni, N codoped 3D np‐graphene shows great potential as an economical catalyst/electrode for metal–air batteries. Abstract : The presence of N facilitates the loading of a high density of isolated Ni single atoms on graphene . The Ni and N codopod 3D nanoporous graphene exhibits greatly enhanced bifunctional oxygen catalytic activities due to the synergetic effect between Ni and N. Due to the superior catalytic performance and structure advantage, a nanoporous graphene‐based all‐solid‐state Zn–air battery exhibits superior performance.